Comparison of the electronic, optical and photocatalytic properties of MoSe2, InN, and MoSe2/InN heterostructure nanosheet-A first-principle study. (15th August 2021) - Sivasamy, Ramesh; Quero, Franck; Paredes-Gil, Katherine; Batoo, Khalid Mujasam; Hadi, Muhammad; Raslam, Emad H.
Abstract: Recently, investigation on two-dimensional (2D) metal dichalcogenides has attracted significant attention owing to their impressive electronic structure and optical properties for optoelectronics and photocatalytic applications. Nevertheless, the higher rate of the photo-generated carriers and the electron-hole recombination process limits their technological applications. A promising strategy may consist of constructing 2D heterostructures that could potentially enhance their photocatalytic activities. This work reports the structure, electronic structure, optical, interfacial, and photocatalytic properties of MoSe2 /InN heterostructure nanosheet. The interfacial interaction between the MoSe2 and the InN layers was the van der Waals bonding type. The valence band edge and conduction band edge positions of consecutive layers were altered near the Fermi level and formed type-II band orientation. The electronic structure and work function results confirmed that heterojunction potentially possesses improved photocatalytic activity. This work provides the basics for the future development of various enhanced heterostructures for photocatalytic applications. Graphical abstract: Figure: Two-dimensional MoSe2/InN heterostructure nanosheet. Image 1 Highlights: MoSe2 and InN sheets interact via vdW forces in the MoSe2 /GaN heterostructure. MoSe2 /InN band structure reveals a p-type semiconductor by type-II band alignment. Optical properties are dominating in 100-plane electric polarization. The workfunction confirms the photocatalytic behavior of the sample.